Institutions and brain drain: the role of business start-up regulations - NGA NDJOBO, Patrick Marie (2020)
The objective of this article is to re-examine the relationship between African institutions and the migration phenomena. Specifically, we analyze the relationship between business start-up regulations and the brain drain from sub-Saharan African (SSA) countries towards those in OECD. Using data from 33 countries, 7 of which belong to OECD, from years 2000, 2005 to 2010, and a gravity model, we firstly show that regulations which control enterprise creation in SSA countries make a positive and significant contribution to brain drain towards OECD countries. Secondly, given the strong association between high unemployment rates and corruption, the combined effect of all the variables is more important than when regulation is considered on its own. According to our results, setting up regulations for effective enterprise creation may retain qualified individuals in Africa, mainly those who are entrepreneurs and have in sight the creation of their own businesses. In addition, regulations, governance and the potential contribution of these entrepreneurs should be taken into account in the setting up of integrated national systems of innovation in African countries, especially in terms of the dynamic processes that occur at the meeting point of the university, industry and government institutional spheres.